Effects of leisure-time and occupational physical activities on 20-year incidence of acute myocardial infarction: mediation and interaction - Wang, Aolin; Arah, Onyebuchi A; Kauhanen, Jussi; Krause, Niklas (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'This study aimed to disentangle the interplay between occupational physical activity (OPA) and leisure-time physical activity (LTPA) in affecting cardiovascular health by examining: (i) interactions between OPA and LTPA and their combined effect on 20-year incidence of acute myocardial infarction (AMI) and (ii) the effect of OPA on AMI that is mediated through LTPA. ' ' METHODS ': 'We analyzed data on 1891 men, aged 42–60 years at baseline, from the prospective Kuopio Ischemic Heart Disease Risk Factor Study. OPA was measured as relative aerobic strain (RAS), accounting for workers’ cardiorespiratory fitness. Averaged 12-month LTPA and potential confounders were assessed by questionnaires. Analyses were stratified by the presence of ischemic heart disease (IHD) at baseline. ' ' RESULTS ': 'We found potential multiplicative, but not additive, interactions between OPA and LTPA among men with IHD. The multivariable Cox model, adjusted for age, education, smoking, alcohol consumption, psychosocial job factors, and participation in an unrelated drug trial, showed that high OPA positively predicted AMI at low LTPA levels for both men with and without IHD: hazard ratio (HR) 1.27 [95% confidence interval (95% CI) 0.96–1.68] and HR 1.59 (95% CI 0.99–1.68), respectively. The combination of high OPA and low LTPA constituted the group associated with the highest risk for AMI, irrespective of IHD status. LTPA was not independently predictive of AMI and did not mediate the impact of OPA on AMI. ' ' CONCLUSIONS ': 'LTPA interacted with OPA on the multiplicative scale only. LTPA did not mediate the effect of OPA on AMI.
Keywords: acute myocardial infarction; coronary heart disease; effect modification; energy expenditure; epidemiology; IHD; interaction; ischemic heart disease; leisure-time; mediation; occupational health; occupational physical activity; physical activity; population-based study; prospective study; relative aerobic strain; relative aerobic workload